Hospital based analytic study of peptic ulcer disease in patients with dyspeptic symptoms - Sharma, SK; Maharjan, DK; Thapa, PB (Kathmandu University Medical Journal, 2010)
Background: Peptic ulcer disease is one of the most common diseases prevalent in developing country like Nepal and with availability of endoscopy there have been increase in diagnosis and therapeutic use of endoscopy. Objective: The aim of this study is to investigate the prevalence of peptic ulcer disease in patient who came for upper gastrointestinal endoscopy in Kathmandu Medical College Teaching Hospital. Materials and methods: All patients who were referred to department of endoscopy from outpatient department (OPD) and inpatient department with symptoms like dyspepsia, upper GI bleeding were included from August 2004 to August 2008. Results: A total of 2761 patient were evaluated, with mean age group of 40.57 years (range 8- 95 years) and with sex distribution of male 1353 (49%) and female 1408 (51%) and racial difference into Aryan 2050 (74.2%) and Mongoloid 771 (25.8%). There were 983 patients (35.60%) with peptic disease which includes erosive gastritis, non erosive gastritis, duodenitis and gastroduodenitis without obvious ulcer. The prevalence of peptic disease with or without ulcer was more common in age group of 20- 49 years (n= 764, 27.67 %) with 70 patient with gastric ulcer (2.5%) and 50 patient with duodenal ulcer (1.8%). There was no significant racial difference among incidence of peptic ulcer (P value= 0.527). Conclusions: Peptic ulcer disease is a significant cause of morbidity in urban population of Nepal with more prevalent of erosive diseases in productive age group (20-49 years). However both male and female have equal incidence of peptic ulcer disease and there was no significant racial difference in its incidence. Key words: Peptic ulcer diseases; Oesophago-gastroduodenoscopy; H. pylori DOI: 10.3126/kumj.v7i2.2706 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 135-138